How to generate popular post headlines on social media? - Zhouxiang Fang; Min Yu; Zhendong Fu; Boning Zhang; Xuanwen Huang; Xiaoqi Tang; Yang Yang (AI Open)
Posts, as important containers of user-generated-content on social media, are of tremendous social influence and commercial value. As an integral component of post, headline has decisive influence on post’s popularity. However, the current mainstream method for headline generation is still manually writing, which is unstable and requires extensive human effort. This drives us to explore a novel research question: Can we automate the generation of popular headlines on social media? We collect more than 1 million posts of 42,447 thousand celebrities from public data of Xiaohongshu, which is a well-known social media platform in China. We then conduct careful observations on the headlines of these posts. Observation results demonstrate that trends and personal styles are widespread in headlines on social medias and have significant contribution to posts’ popularity. Motivated by these insights, we present MEBART, which combines Multiple preference-Extractors with Bidirectional and Auto-Regressive Transformers (BART), capturing trends and personal styles to generate popular headlines on social medias. We perform extensive experiments on real-world datasets and achieve SOTA performance compared with advanced baselines. In addition, ablation and case studies demonstrate that MEBART advances in capturing trends and personal styles.